Voter mobilisation in the echo chamber: Broadband internet and the rise of populism in Europe - Max Schaub; Davide Morisi (European Journal of Political Research, 2020)
Can the diffusion of broadband internet help explain the recent success of populist parties in Europe? Populists cultivate an anti-elitist communication style, which, they claim, directly connects them with ordinary people. The internet therefore appears to be the perfect tool for populist leaders. This study shows that this notion holds up to rigorous empirical testing. Drawing on survey data from Italy and Germany, a positive correlation is found between use of the internet as a source of political information and voting for populist parties. By instrumenting internet use with broadband coverage at the municipality level, the study then demonstrates that this relationship is causal. The findings suggest that part of the rise of populism can be attributed to the effect of online tools and communication strategies made possible by the proliferation of broadband access.
Keywords: 320; populism; broadband internet; voting behaviour; Italy; Germany